Development of public administration methods in the field of green economy: The case of Kazakhstan - Kirbassova, Laila; Shukeyev, Umirzak; Turekulova, Dametken; Saimagambetova, Gaukhar; Mendaliyeva, Shynar (International Journal of Innovative Research and Scientific Studies, 2025)
In the context of global environmental challenges and climate change, the transition to a green economy is becoming a strategic priority for Kazakhstan. The national concept, adopted in 2013, is focused on abandoning the carbon model, increasing resource efficiency and developing environmentally sound technologies. To achieve these goals, it is necessary to transform public administration with the introduction of flexible, digital and knowledge-based mechanisms, as well as a system of monitoring, forecasting and public participation that promotes sustainable development. The purpose of the study is to determine the dynamics of final electricity consumption in agriculture and forestry of the Republic of Kazakhstan in the context of the implementation of the state policy of transition to a green economy and to develop state planning tools aimed at improving energy efficiency and reducing the carbon footprint. The design of the study is the analysis of a time series of statistical data for the period 2011-2024 in order to identify trends in electricity consumption in agriculture, and the construction of a predictive model for 2025-2027 based on mathematical and statistical methods. The article examines the dynamics of final electricity consumption in agriculture and forestry of the Republic of Kazakhstan for the period 2011-2024 in the context of the formation of state policy in the field of green economy. A statistical analysis of the time series has been performed, including checking for a trend component, calculating the Irwin criterion, and constructing a linear regression model using the least squares method. The presence of a stable upward trend has been established, which is confirmed by the results of the analysis of the sequences and residuals of the model. The forecast values for 2025-2027 indicate a further increase in consumption, which underlines the relevance of digitalization and the introduction of energy-efficient technologies in agriculture. The developed model makes it possible to estimate future loads on the energy system and can be used in the state planning system when developing measures to reduce the carbon footprint in the agro-industrial complex. The results obtained confirm the need for flexible management solutions at the regional level aimed at supporting sustainable resource management practices and developing a digital infrastructure for monitoring energy consumption in the agricultural sector.